Social skills of street children emerging from cooperative play - Dela Cruz, Anton Miguel T.; Sigaya, Krishna Elizabeth T.
The cooperative play of street children provides understanding on their social functions. These children play and explore in an unconventional environment. The researchers discuss the play environment, play activities, and the social skills emerging from their own cooperative play within their play environment. Literature suggests that street children exhibit characteristics of resourcefulness and camaraderie through their play. Using a naturalistic and non-participant qualitative research through three observations and interviews to ten street children within Quezon City ages five to eight, findings suggested that children accommodate their play to the materials and features of their environment and street children used their cooperative play as means of practicing and developing various social skills.